Two new species in the orb-weaving spider genus Larinia Simon, 1874 (Araneae, Araneidae) from Western Australia - Framenau, Volker W.; Castanheira, Pedro De S. (Zootaxa, 2022)
Two new species in the orb-weaving spider genus Larinia Simon, 1874 are described, L. sexta n. sp. and L. tumulus n. sp. This elevates the Australian number of described species in the genus to seven. With the exception of two females of L. sexta n. sp. recorded from mainland Western Australia, both species have so far exclusively been found on Barrow Island, 50 km off the north-western Western Australian coast where a third species, L. montagui Hogg, 1914, also occurs. Both new species appear to favour spinifex (Triodia spp.) grassland, but specimen numbers in collections are too low to accurately characterize life history patterns and habitat preferences.